Enhancing resilience: Model-based simulations - D'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2022)
Since several years, the fragility of global supply chains (GSCs) is at historically high levels. In the same time, the landscape of hybrid threats is expanding. This paper aims to assess the economies' foreign input reliance and foreign market reliance, identify possible vulnerabilities by simulating shocks to GSCs in presence of uncertainty. We stress test supply chains by simulating most demanding circumstances and crystallise relevant, effective and efficient policy solutions. Conceptually, we employ a newly developed modelling framework, which is specially designed to account for the increasingly inter-dependent GSCs and study resilience and robustness in presence of hybrid shocks. The scalable data model is parameterised by combining World-Input Output Tables with those from the Inter-Country Input-Output. We study how the decision of a GSC input sourcing diversification changes in the presence of uncertainty and what are the implications for supply chain robustness and resilience. Model-based simulations facilitate decision making by providing interoperable and directly comparable quantifications of counterfactual resilience and robustness strategic choices and allow to identify policy solutions towards baseline resilience requirements.
Keywords: E7; F02; F12; F13; L15; 330; Resilience; Global Supply Chain; model; uncertainty; risk; ambiguity; World-Input Output Tables